Dysregulated Wnt signalling and recurrent mutations of the tumour suppressor RNF43 in early gastric carcinogenesis. Issue 3 (November 2016) - Min, Byung‐Hoon; Hwang, Jinha; Kim, Nayoung KD; Park, Gibeom; Kang, So Young; Ahn, Sangjeong; Ahn, Soomin; Ha, Sang Yun; Lee, Yun Kyung; Kushima, Ryoji; Van Vrancken, Michael; Kim, Min Jung; et al.
Abstract: Several recurrent mutations and epigenetic changes have been identified in advanced gastric cancer, but the genetic alterations associated with early gastric carcinogenesis and malignant transformation remain unclear. We investigated the genomic and transcriptomic landscape of adenomas with low‐grade dysplasia (LGD) and high‐grade dysplasia (HGD), and intestinal‐type early gastric cancer (EGC). The results were validated in an independent cohort that included EGCs directly adjacent to adenoma (EGC‐adenomas) that were in the process of malignant transformation, and de novo EGCs that do not seem to have been derived from adenoma. The expression patterns clearly divided into normal, LGD, and EGC, whereas those of HGD overlapped with LGD or EGC. These results suggest that HGD is the critical stage determining malignant transformation. We found that genes related to focal adhesion and extracellular matrix receptor interaction pathways were upregulated as LGD progressed to EGC, whereas canonical Wnt signalling and peroxisome proliferator‐activated receptor (PPAR) signalling pathway genes were downregulated in EGC. Genomic alterations such as somatic mutation, gene fusion and copy number variation increased gradually from LGD to EGC. APC mutations were present in 67% of LGDs, 58% of HGDs, and 18% of EGCs. RNF43 mutations were present only in HGD and EGC, and TP53 mutations were present only in EGC. In a validation cohort, RNF43 mutations were present in 35.2% of EGC‐adenomas, but in only 8.6% of de novo EGCs. This is the first study to investigate the genomic and transcriptomic landscape of multistep gastric carcinogenesis. We investigated important alterations and their related pathways in each step as tumours progressed from LGD to HGD and eventually to EGC. We suggest that mutations and downregulation of RNF43 may play a critical role in the transition from adenoma to carcinoma. Given these findings and Wnt dependency in tumours with RNF43 mutation, intestinal‐type gastric cancer or adenoma with RNF43 mutation might represent a promising indication for Wnt‐targeted agents. Copyright © 2016 Pathological Society of Great Britain and Ireland. Published by John Wiley & Sons, Ltd.